2021
DOI: 10.1182/bloodadvances.2021004853
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-derived macrophages for efficientStaphylococcus aureusclearance in a murine pulmonary infection model

Abstract: Primary or secondary immunodeficiencies are characterized by disruption of the cellular and humoral immunity. Respiratory infections are a major cause of morbidity and mortality among immunodeficient or immunocompromised patients with Staphylococcus aureus being a common offending organism. We here propose an adoptive macrophage transfer approach aiming to enhance impaired pulmonary immunity against S. aureus. Our studies, using human induced pluripotent stem cells (iPSC)-derived macrophages (iMφ) demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…iMph infectability with various pathogens has been documented and used to study the molecular basis of macrophage-pathogen interactions. Future developments will likely include the elaboration of approaches to infectious disease treatment based on the use of “native” [ 46 , 96 , 98 ] or genetically engineered [ 96 ] iMphs. Drug screening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…iMph infectability with various pathogens has been documented and used to study the molecular basis of macrophage-pathogen interactions. Future developments will likely include the elaboration of approaches to infectious disease treatment based on the use of “native” [ 46 , 96 , 98 ] or genetically engineered [ 96 ] iMphs. Drug screening.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Ackermann and co-authors demonstrated that human iMphs co-administered with P. aeruginosa to immunodeficient humanized mice prevented the development of P. aeruginosa infection; when injected shortly after the pathogen, iMphs rescued mice from severe infection [ 46 ]. More recently, the same group reported that intrapulmonary injection of human iMphs significantly reduced bacterial load and local pulmonary inflammation in immunodeficient mice challenged with Staphilococcus aureus 4 h prior to cell transfer [ 98 ]. Of note, iMphs responded to S. aureus infection by a profound upregulation of inflammatory genes soon after the infection, but quickly restored their stationary state, which is considered as a feature important for future iMph therapeutic use.…”
Section: Modeling Macrophage-pathogen Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the unmet clinical need and the high morbidity and mortality of S. aureus in immunodeficient patients, Hashtchin et al 2 recently explored the applicability of a macrophage-based immunotherapy against pulmonary S. aureus infections in immunodeficient condition. Using a scalable production platform, the authors generated a highly pure population of macrophages derived from human-induced pluripotent stem cells (iPSCs).…”
mentioning
confidence: 99%
“…While immunodeficient mice infected via intratracheal instillation of S. aureus developed extensive pulmonary infection, infected immunodeficient mice treated with iPSC-derived macrophages showed sign of a significantly less severe infection, with reduced pulmonary bacterial load, decreased monocyte and granulocyte infiltration, and overall less edema and tissue damage (Figure 1 ). 2 Interestingly, the authors compared iPSC-derived versus peripheral blood monocyte-derived macrophages as potential source of cell immunotherapy. A significantly stronger antimicrobial response was provided by iPSC-derived macrophages, as suggested by the higher secretion of IL-6, a crucial pro-inflammatory cytokine driver of immunity against S. aureus .…”
mentioning
confidence: 99%